Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

(3x-2y)dy+(x+y-5)dx=0

Differential Equations
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
\[\newcommand \p \newcommand \p \dd [1] { \,\mathrm d#1 } % infinitesimal \p \de [2] { \frac{ \mathrm d #1}{\mathrm d#2} } % first order derivative \small\begin{align} (3x-2y)\dd y+(x+y-5)\dd x &=0 \\ \de yx &=\frac{5-x-y}{3x-2y} \\ \\ \text{let } x=X+p \\ y=Y+q \\ \de yx=\de YX \\ \\ \de YX &=\frac{5-(X+p)-(Y+q)}{3(X+p)-2(Y+q)} \\ \de YX &=\frac{-X-Y+(5-p-q)}{3X-2Y+(3p-2q)} \\ \\ 5-p-q=0 &\to q=5-p \\ 3p-2q=0 &\to 3p-2(5-p)=0 \to 5p-10=0 &\to p=2 \\ 5-2-q=0 &\to 3-q=0 \to q=3 \\ \\ \de YX &=\frac{-X-Y}{3X-2Y} \\ \de YX &=\frac{-1-Y/X}{3-2Y/X} \\ \\ \text{let }Y/X=V \\ Y=VX \\ Y'=V'X+V \\ \\ V'X+V &=\frac{-1-V}{3-2V} \\ V'X &=\frac{-1-V}{3-2V}-V\frac{3-2V}{3-2V} \\ V'X &=\frac{2V^2-4V-1}{3-2V} \\ \frac{3-2V}{2V^2-4V-1}\dd V &=\frac{\dd X}X \\ \int\frac{1}{2V^2-4V-1}\dd V +\int\frac{2-2V}{2V^2-4V-1}\dd V &=\int\frac{\dd X}X \\ \int\frac{1}{(\sqrt2V-\sqrt2)^2-3}\dd V -\frac12\int\frac{4V-4}{2V^2-4V-1}\dd V &=\int\frac{\dd X}X \\ -\frac13\int\frac{1}{1-\left(\sqrt{\tfrac23}(V-1)\right)^2}\dd V -\tfrac12\ln|2V^2-4V-1| &=\ln|X|+c \\ -\tfrac13\sqrt{\tfrac32}\tanh^{-1}\left(\sqrt{\tfrac23}(V-1)\right) -\tfrac12\ln|2V^2-4V-1| &=\ln|X|+c \\ -\tfrac1{\sqrt6}\tanh^{-1}\left(\sqrt{\tfrac23}\big(\tfrac{y-3}{x-2}-1\big)\right) -\tfrac12\ln\left|2(\tfrac{y-3}{x-2})^2-4(\tfrac{y-3}{x-2})-1\right| &=\ln|x-2|+c \end{align} \]
Checking answer? O.o
is there a more elegant method ?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

lol
subtract, integrate and then solve for y
Probably not. I would have done basically the same thing except I might have done it right off the bat. y = vx and dy = v'x + vx' and went from there.
'x=dx/dx=1
No, there isn not. :( in my opinion this is one of those problems best left to a computer. :) http://www.wolframalpha.com/input/?i=(3x-2y)dy%2B(x%2By-5)dx%3D0&t=crmtb01
It's a question from a second year university differential equations course tutorial week 1
Seems pretty standard, really. Wish I could say Ive seen one of those y = vx dy = v'x + vx' subs that was pretty.
it looks like you drew an ostrich

Not the answer you are looking for?

Search for more explanations.

Ask your own question